Plan de negocio del yogurt griego natural para su posicionamiento en la zona sur de Manabí - Bravo Marcillo, Junior Yoel (2022)
The present investigation was carried out with the objective of designing a business plan for the expansion of natural Greek yogurt in the southern region of Manabí. It is worth mentioning the contribution this study provided the company by allowing it to develop future ideas, facilitate the organization of projects and make the company more concrete once the stages are executed. To develop said process, three phases were determined necessary, the first required a market study, the application of a questionnaire and study were instrumental. The collection of information related events consumer behaviors criteria and customs of residents were favored. A response is generated about how the product was received by the public. The second phase required a technical, operational study, which defined the costs, materials and supplies necessary to start the company. Finally, the third phase consisted of an economic study which made it possible, resulting in a positive Internal Rate of Return (IRR) that is the percentage of the discount as well as the Net Present Value (NPV).